In vivo imaging of mitochondrial function in normal, glaucoma suspect, and glaucoma eyes - René Caro; Andrew Chen; Raghu Mudumbai; Eric Duerr; Philip P. Chen; Karine D. Bojikian (PLoS ONE, 2025)
To investigate macula and optic nerve head (ONH) mitochondrial metabolic activity using flavoprotein fluorescence (FPF) in normal, glaucoma suspect (GS), and open-angle glaucoma (OAG) eyes we performed a cross-sectional, observational study of FPF in normal, GS, and OAG eyes. The macula and ONH of each eye was scanned and analyzed with a commercially available FPF measuring device (OcuMet Beacon, OcuSciences Inc., Ann Arbor, MI). One-way analysis of variance was used to compare macula and ONH FPF scores between groups. Linear regression models investigated the correlation between FPF scores and structural and functional parameters. We included 25 normal, 16 GS, and 54 OAG eyes. The average age in years ± SD for normal, GS, and OAG groups was 60.6 ±17.4, 67.8 ± 10.3, and 67.9 ± 11.6, respectively (P = 0.064). There was no significant difference in gender, race/ethnicity, visual acuity, and intraocular pressure between groups. OAG eyes had larger cup-to-disc ratio, thinner retinal nerve fiber and macula thicknesses, and worse visual field indices compared to normal and GS eyes (P ≤ 0.018). There was no significant difference in any FPF metric between the study groups in either the macula or the ONH, despite normalizing FPF data for structural differences between groups (e.g. retinal nerve fiber layer and ganglion cell-inner plexiform layer thickness). In conclusion, no significant differences in metabolic activity as measured by FPF were found in macula and ONH FPF scores using the integrated clinician report generator between normal, GS, and OAG eyes. Further research is needed to evaluate the role of mitochondrial metabolic activity measurements in glaucoma.